2016
DOI: 10.5902/2236117020025
|View full text |Cite
|
Sign up to set email alerts
|

Consciência e Atitude Ambiental em Estudantes de Instituições de Ensino Técnico e Tecnológico

Abstract: Environmental education is a powerful tool for forming collective environmental awareness from primary school to higher education level. Based on this, this study aims to investigate environmental awareness and environmental behavior among students of a technological educational institution. Using the NEP Scale (Dunlap et al., 2010) through a questionnaire with students it sought to examine the relationship between consciousness and environmental behavior through variables like course, semester, gender and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…In addition, the NEP scale has been used in conjunction with other scales to determine proenvironmental attitudes such as: in various populations [29 ,35], in environmental education [36], in agroindustrial actions [37], in tourism [38], in student behavior [39,40], in pro-environmental behaviors [15], in species conservation actions [41], in academic, national and international actions, etc.…”
Section: Application Of the Nep Scalementioning
confidence: 99%
“…In addition, the NEP scale has been used in conjunction with other scales to determine proenvironmental attitudes such as: in various populations [29 ,35], in environmental education [36], in agroindustrial actions [37], in tourism [38], in student behavior [39,40], in pro-environmental behaviors [15], in species conservation actions [41], in academic, national and international actions, etc.…”
Section: Application Of the Nep Scalementioning
confidence: 99%
“…A escala do NEP foi obtida após a análise da literatura relevante sobre o tema, escolhendo a proposta de Dunlap et al (2000). Primeiro o questionário foi traduzido do inglês para o português e comparado com algumas outras aplicações em português e espanhol (Guedes et al, 2016;Díaz;Vélez, 2014;Teixeira et al, 2016;Talamini et al, 2017;Talamini, 2019;Reis Neto et al, 2021). O questionário foi dividido em duas seções: a primeira identificou o perfil acadêmico (sexo, faixa de idade e curso), mantendo-se o seu anonimato, e a segunda seção com 15 declarações avaliadas pela escala de sete pontos de Likert de concordância (1= Discordo totalmente a 7=…”
Section: Introductionunclassified
“…Humanity faces serious challenges in regards to sustainability: from an environmental standpoint, climate change and the scarcity of natural resources; and from a societal point of view, there is an increase in inequality (Lorek & Fuchs, 2013). The perception that natural resources are finite and that their extinction threatens human survival has brought political, social, economic and scientific repercussions (Teixeira, Silva-Filho & Meireles, 2016). Through these repercussions, it was observed that there is an urgent need to improve the sustainability practices of both families and organizations (Doyle & Davies, 2013).…”
Section: Introductionmentioning
confidence: 99%